Correlating Media Literacy Skills of Library Staff and Service Delivery in Academic Libraries in Taraba State, Nigeria - Onuoha, Juliet; Chukwueke, Chukwuemeka (Communicate: Journal of Library and Information Science, 2023)
The study correlated the media literacy skills and service delivery of library staff in academic libraries in Taraba State, Nigeria. The correlational research design was adopted in studying 112 library staff drawn from 11 academic libraries in Taraba State. A researcher-made questionnaire was used for data collection. A total of 112 copies of the questionnaire were administered but 109 were retrieved. Data was analyzed using descriptive and inferential statistics. The single null hypothesis was tested at 0.05 level of significance using the linear regression. Consequently, the strength of relationship between variables was decided using the Creswell correlational ranking and results presented in frequency tables. Findings of the study shows that media literacy skills possessed by the library staff was low as they were only skillfulcomparing information on different media, detecting fake news on the media, among other skills. Furthermore, result showed a correlational value of 0.03 and hypothesis yielded a p-value of 0.76. This shows that there is a positive very low and insignificant relationship between media literacy skills of library staff and service delivery in academic libraries in Taraba State, Nigeria. Based on the findings, the study recommends that library authorities should intensify efforts in creating the understanding of media literacy skills, their essence and application to enable the library staff to acquire more of the skills as well as apply them in the discharge of their duties, among other things.